تطوير مقياس التشوه المعرفي لـ يوركا و دي توماسو باستخدام نموذج سلم التقدير لنظرية الاستجابة للفقرة - بابان, وليد خالد عبدالكريم (Sulaimani Journal for Humanities, 2018)
The current research aims at using Rating Scale Model (RSM), one of the extensions of the Single Master Teacher model in the development of the cognitive deformity scale for middle school students. To achieve this goal, the researcher (CDI) for Yurica & DiTomaso, 2001, which was adapted by Saadawi, 2014, adopted the local environment. This list consists of (69) quasi- A random stratified sample of (300) male and female students was recruited from the preparatory school at the Education Directorate in Kirkuk. The assumptions of the theory of response to item the logarithmic clause, the most important of which are the one-dimensional borrowing, have been verified through the global analysis of the scale in the basic components method. One factor has been obtained that has a meaningful interpretation of the scale. The same factor has been adopted at the lower limit of Gtman, (1), and the dependence of the Bert-Banks test on the ratio of the saturation of the parameters of the scale to the general factor. The researcher also adopted another method to achieve the one-dimensional measurement of Pearson correlation coefficient To The internal coefficient between the scales of the scale and that they are oriented to measure one attribute where the coefficient coefficient coefficient ranged between (0.71) and (0.38). As for verification of the assumption of local independence, the researcher conducted the global analysis of the scale in a way (verifying the reliability matrix of the paragraphs). In order to analyze the measurement data, the researcher adopted the estimation scale model using the computerized program (ConstructMap-4.6). The results of the statistical analysis showed that the extent of the difficulty of (location) of the paragraphs was (2,862) to (-2,109), with an average error rating (0.037) after deleting (3) paragraphs or the value of tau () -2,391, -1,008, 0,671, 1,945) and on the sequence of the least gradient. The capacity of individuals ranged from (1,986) to (-2,416). For the stability of the information, it reached 0.91, and the stability of the scales of the scale (0.75) and the stability of the power rating reached (0.90). With these results, the researchers found the effectiveness of the model in the development of the (CDI).
Keywords: Cognitive Distortion; Scale Model; Response Item Theory